Dr William Coley and tumour regression: a place in history or in the future. Issue 938 (5th January 2004) - Hoption Cann, S A; van Netten, J P; van Netten, C
Abstract : Spontaneous tumour regression has followed bacterial, fungal, viral, and protozoal infections. This phenomenon inspired the development of numerous rudimentary cancer immunotherapies, with a history spanning thousands of years. Coley took advantage of this natural phenomenon, developing a killed bacterial vaccine for cancer in the late 1800s. He observed that inducing a fever was crucial for tumour regression. Unfortunately, at the present time little credence is given to the febrile response in fighting infections—no less cancer. Rapidly growing tumours contain large numbers of leucocytes. These cells play a part in both defence and repair; however, reparative functions can also support tumour growth. Intratumoural infections may reactivate defensive functions, causing tumour regression. Can it be a coincidence that this method of immunotherapy has been "rediscovered" repeatedly throughout the centuries? Clearly, Coley's approach to cancer treatment has a place in the past, present, and future. It offers a rare opportunity for the development of a broadly applicable, relatively inexpensive, yet effective treatment for cancer. Even in cases beyond the reach of conventional therapy, there is hope.